A facile route for preparation of CdS nanoparticles - Maleki, M.; Sasani Ghamsari, M.; Mirdamadi, Sh.; Ghasemzadeh, R. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
CdS nanoparticles have been synthesized by a chemical reaction route using ethylenediamine as a complexing agent. The nanoparticles were characterized using techniques such as X-ray powder diffraction (XRD), scanning electron microscope (SEM), UV–VIS absorption spectroscopy, and photoluminescence spectroscopy. The absorption edge for the bulk hexagonal CdS is at 512 nm (2.42 eV). Comparing with the bulk CdS, it is believed that the blue shift in the absorption peak was caused by the quantum confinement effect. Photoluminescence measurements indicate CdS nanoparticles show fluorescence band with a maximum close to 315 nm.